The supremum of S is 2, and the infimum of S is -2.
The set S consists of values obtained by evaluating the function 2sin(2x) for all x values between -π/2 and π/2. In this range, the sine function reaches its maximum value of 1 and its minimum value of -1. Multiplying these values by 2 gives us the range of S, which is from -2 to 2.
To find the supremum, we need to determine the smallest upper bound for S. Since the maximum value of S is 2, and no other value in the set exceeds 2, the supremum of S is 2.
Similarly, to find the infimum, we need to determine the largest lower bound for S. The minimum value of S is -2, and no other value in the set is less than -2. Therefore, the infimum of S is -2.
In summary, the supremum of S is 2, representing the smallest upper bound, and the infimum of S is -2, representing the largest lower bound.
Learn more about supremum
brainly.com/question/30967807
#SPJ11
3. Given f(x) = 2x-3 and g(x) = 5x + 4, use composite (f° g)(x) = f(g(x)) in the following.
A. Find composite (f° g)(x) =
B. Find composite (g° f)(x) =
C. Find composite (f° g)(-3)=
4. Given f(x) = x2 - 8x - 9 and g(x) = x^2+6x + 5, use composite (f° g)(x) = f(g(x)) in the following.
A. Find composite (fog)(0) =
B. Find composite (fog)(1) =
C. Find composite (g° f)(1) =
5. An envelope is 4 cm longer than it is wide. The area is 96 cm². Find the length & width.
6. Three consecutive even integers are such that the square of the third is 76 more than the square of the second. Find the three integers.
The three consecutive even integers are -38, -36, and -34.
Given f(x) = 2x-3 and g(x) = 5x + 4, the composite of f° g(x) = f(g(x)) can be calculated as follows:
Solution: A. Composite (f° g)(x):f(x) = 2x - 3 and g(x) = 5x + 4
Let's substitute the value of g(x) in f(x) to obtain the composite of f° g(x) = f(g(x))f(g(x))
= f(5x + 4)
= 2(5x + 4) - 3
= 10x + 5
B. Composite (g° f)(x):f(x)
= 2x - 3 and g(x)
= 5x + 4
Let's substitute the value of f(x) in g(x) to obtain the composite of g° f(x) = g(f(x))g(f(x))
= g(2x - 3)
= 5(2x - 3) + 4
= 10x - 11
C. Composite (f° g)(-3):
Let's calculate composite of f° g(-3)
= f(g(-3))f(g(-3))
= f(5(-3) + 4)
= -10 - 3
= -13
Given f(x) = x² - 8x - 9 and
g(x) = x²+ 6x + 5,
the composite of f° g(x) = f(g(x)) can be calculated as follows:
Solution: A. Composite (fog)(0):f(x) = x² - 8x - 9 and g(x)
= x² + 6x + 5
Let's substitute the value of g(x) in f(x) to obtain the composite of f° g(x) = f(g(x))f(g(x))
= f(x² + 6x + 5)
= (x² + 6x + 5)² - 8(x² + 6x + 5) - 9
= x⁴ + 12x³ - 31x² - 182x - 184
B. Composite (fog)(1):
Let's calculate composite of f° g(1) = f(g(1))f(g(1))
= f(1² + 6(1) + 5)= f(12)
= 12² - 8(12) - 9
= 111
C. Composite (g° f)(1):
Let's calculate composite of g° f(1) = g(f(1))g(f(1))
= g(2 - 3)
= g(-1)
= (-1)² + 6(-1) + 5= 0
The length and width of an envelope can be calculated as follows:
Solution: Let's assume the width of the envelope to be x.
The length of the envelope will be (x + 4) cm, as per the given conditions.
The area of the envelope is given as 96 cm².
So, the equation for the area of the envelope can be written as: x(x + 4) = 96x² + 4x - 96
= 0(x + 12)(x - 8) = 0
Thus, the width of the envelope is 8 cm and the length of the envelope is (8 + 4) = 12 cm.
Three consecutive even integers whose square difference is 76 can be calculated as follows:
Solution: Let's assume the three consecutive even integers to be x, x + 2, and x + 4.
The square of the third integer is 76 more than the square of the second integer.x² + 8x + 16
= (x + 2)² + 76x² + 8x + 16
= x² + 4x + 4 + 76x² + 4x - 56
= 0x² + 38x - 14x - 56
= 0x(x + 38) - 14(x + 38)
= 0(x - 14)(x + 38)
= 0x = 14 or
x = -38
To know more about integers visit:
https://brainly.com/question/490943
#SPJ11
What is the area of this figure?
Enter your answer in the box. Cm² 4 cm at top 5cm to right 5cm at bottom
The area of the given figure, we can divide it into two separate shapes: a rectangle and a right triangle. The area of the given figure is 30 cm².
First, let's calculate the area of the rectangle. The width of the rectangle is 5 cm, and the height is 4 cm. The area of a rectangle is given by the formula: A = length × width. Therefore, the area of the rectangle is:
Area of rectangle = 5 cm × 4 cm = 20 cm².
Next, let's calculate the area of the right triangle. The base of the triangle is 5 cm, and the height is 4 cm. The area of a triangle is given by the formula: A = 0.5 × base × height. Therefore, the area of the right triangle is: Area of triangle = 0.5 × 5 cm × 4 cm = 10 cm².
To find the total area of the figure, we add the area of the rectangle and the area of the triangle:
Total area = Area of rectangle + Area of triangle = 20 cm² + 10 cm² = 30 cm².
Therefore, the area of the given figure is 30 cm².
Learn more about rectangle here
https://brainly.com/question/2607596
#SPJ11
If a media planner wishes to run 120 adult 18-34 GRPS per week,
and if the Cpp is $2000 then the campaign will cost the advertiser
_______per week.
If a media planner wishes to run 120 adult 18-34 GRPS per week, the frequency of the advertisement needs to be 3 times per week.
The Gross Rating Point (GRP) is a metric that is used in advertising to measure the size of an advertiser's audience reach. It is measured by multiplying the percentage of the target audience reached by the number of impressions delivered. In other words, it is a calculation of how many people in a specific demographic will be exposed to an advertisement. For instance, if the GRP of a particular ad is 100, it means that the ad was seen by 100% of the target audience.
Frequency is the number of times an ad is aired on television or radio, and it is an essential aspect of media planning. A frequency of three times per week is ideal for an advertisement to have a significant impact on the audience. However, it is worth noting that the actual frequency needed to reach a specific audience may differ based on the demographic and the product or service being advertised.
Learn more about Gross Rating Point (GRP) here: https://brainly.com/question/29454398
#SPJ11
Find the inverse function of y = (x-3)2 + 7 for x > 3..
a. y¹ = 7+ √x-3
b. y¹=3-√x+7
c. y¹=3+ √x - 7
d. y¹=3+ (x − 7)²
The correct option is:
c. y¹ = 3 + √(x - 7)
To find the inverse function of y = (x - 3)^2 + 7 for x > 3, we can follow these steps:
Step 1: Replace y with x and x with y in the given equation:
x = (y - 3)^2 + 7
Step 2: Solve the equation for y:
x - 7 = (y - 3)^2
√(x - 7) = y - 3
y - 3 = √(x - 7)
Step 3: Solve for y by adding 3 to both sides:
y = √(x - 7) + 3
So, the inverse function of y = (x - 3)^2 + 7 for x > 3 is y¹ = √(x - 7) + 3.
Therefore, the correct option is:
c. y¹ = 3 + √(x - 7)
Learn more about inverse function here
https://brainly.com/question/29141206
#SPJ11
Bearing used in an automotive application is supposed to have a nominal inside diameter 1.5 inches. A random sample of 25 bearings is selected, and the average inside diameter of these bearings is 1.4975 inches. Bearing diameter is known to be normally distributed with standard deviation σ=0.1 inch. We want to test the following hypothesis at α=0.01. H0:μ=1.5,H1:μ=1.5 (a) Calculate the type II error if the true mean diameter is 1.55 inches. (b) What sample size would be required to detect a true mean diameter as low as 1.55 inches if you wanted the power of the test to be at least 0.9 ?
(a) Without knowing the effect size, it is not possible to calculate the type II error for the given hypothesis test. (b) To detect a true mean diameter of 1.55 inches with a power of at least 0.9, approximately 65 bearings would be needed.
(a) If the true mean diameter is 1.55 inches, the probability of not rejecting the null hypothesis when it is false (i.e., the type II error) depends on the chosen significance level, sample size, and effect size. Without knowing the effect size, it is not possible to calculate the type II error.
(b) To calculate the required sample size to detect a true mean diameter of 1.55 inches with a power of at least 0.9, we need to know the chosen significance level, the standard deviation of the population, and the effect size.
Using a statistical power calculator or a sample size formula, we can determine that a sample size of approximately 65 bearings is needed.
to know more about hypothesis test, visit:
brainly.com/question/32874475
#SPJ11
What is the value of θ for the acute angle in a right triangle? sin(θ)=cos(53°) Enter your answer in the box. θ= °
Answer:
the value of θ for the acute angle in a right triangle, where sin(θ) = cos(53°), is 37 degrees.
Step-by-step explanation:
In a right triangle, one of the angles is always 90 degrees, which is the right angle. The acute angle in a right triangle is the angle that is smaller than 90 degrees.
To find the value of θ for the acute angle in a right triangle, given that sin(θ) = cos(53°), we can use the trigonometric identity:
sin(θ) = cos(90° - θ)
Since sin(θ) = cos(53°), we can equate them:
cos(90° - θ) = cos(53°)
To find the acute angle θ, we solve for θ by equating the angles inside the cosine function:
90° - θ = 53°
Subtracting 53° from both sides:
90° - 53° = θ
θ= 37°
Therefore, the value of θ for the acute angle in a right triangle, where sin(θ) = cos(53°), is 37 degrees.
In the figure, the square ABCD and the AABE are standing on the same base AB and between the same parallel lines AB and DE. If BD = 6 cm, find the area of AEB.
To find the area of triangle AEB, we use base AB (6 cm) and height 6 cm. Applying the formula (1/2) * base * height, the area is 18 cm².
To find the area of triangle AEB, we need to determine the length of the base AB and the height of the triangle. Since both square ABCD and triangle AABE is standing on the same base AB, the length of AB remains the same for both.
We are given that BD = 6 cm, which means that the length of AB is also 6 cm. Now, to find the height of the triangle, we can consider the height of the square. Since AB is the base of both the square and the triangle, the height of the square is equal to AB.
Therefore, the height of triangle AEB is also 6 cm. Now we can calculate the area of the triangle using the formula: Area = (1/2) * base * height. Plugging in the values, we get Area = (1/2) * 6 cm * 6 cm = 18 cm².
Thus, the area of triangle AEB is 18 square centimeters.
For more questions on the area of a triangle
https://brainly.com/question/30818408
#SPJ8
Which of the following lines is parallel to the line 3x+6y=5?
A. y=2x+6
B. y=3x-2
C. y= -2x+5
D. y= -1/2x-5
E. None of the above
The correct answer is B. y=3x-2.
The slope of a line determines its steepness and direction. Parallel lines have the same slope, so for a line to be parallel to 3x+6y=5, it should have a slope of -1/2. Since none of the given options have this slope, none of them are parallel to the line 3x+6y=5. This line has the same slope of 3 as the given line, which makes them parallel.
Learn more about Parallel lines here
https://brainly.com/question/19714372
#SPJ11
Jocelyn estimates that a piece of wood measures 5.5 cm. If it actually measures 5.62 cm, what is the percent error of Jocelyn’s estimate?
Answer:
The percent error is -2.1352% of Jocelyn's estimate.
(a) Find the work done by a force 5 i^ +3 j^ +2 k^ acting on a body which moves from the origin to the point (3,−1,2). (b) Given u =− i^ +2 j^ −1 k^and v = 2l −1 j^ +3 k^ . Determine a vector which is perpendicular to both u and v .
a) The work done by the force F = 5i + 3j + 2k on a body moving from the origin to the point (3, -1, 2) is 13 units.
b) A vector that is perpendicular to both u = -i + 2j - k and v = 2i - j + 3k is -6i - 7j - 3k.
a) The work done by a force F = 5i + 3j + 2k acting on a body that moves from the origin to the point (3, -1, 2) can be determined using the formula:
Work done = ∫F · ds
Where F is the force and ds is the displacement of the body. Displacement is defined as the change in the position vector of the body, which is given by the difference in the position vectors of the final point and the initial point:
s = rf - ri
In this case, s = (3i - j + 2k) - (0i + 0j + 0k) = 3i - j + 2k
Therefore, the work done is:
Work done = ∫F · ds = ∫₀ˢ (5i + 3j + 2k) · (ds)
Simplifying further:
Work done = ∫₀ˢ (5dx + 3dy + 2dz)
Evaluating the integral:
Work done = [5x + 3y + 2z]₀ˢ
Substituting the values:
Work done = [5(3) + 3(-1) + 2(2)] - [5(0) + 3(0) + 2(0)]
Therefore, the work done = 13 units.
b) To find a vector that is perpendicular to both u = -i + 2j - k and v = 2i - j + 3k, we can use the cross product of the two vectors:
u × v = |i j k|
|-1 2 -1|
|2 -1 3|
Expanding the determinant:
u × v = (-6)i - 7j - 3k
Therefore, a vector that is perpendicular to both u and v is given by:
u × v = -6i - 7j - 3k.
Learn more about force
https://brainly.com/question/30507236
#SPJ11
Consider a radioactive cloud being carried along by the wind whose velocity is
v(x, t) = [(2xt)/(1 + t2)] + 1 + t2.
Let the density of radioactive material be denoted by rho(x, t).
Explain why rho evolves according to
∂rho/∂t + v ∂rho/∂x = −rho ∂v/∂x.
If the initial density is
rho(x, 0) = rho0(x),
show that at later times
rho(x, t) = [1/(1 + t2)] rho0 [(x/ (1 + t2 ))− t]
we have shown that the expression ρ(x,t) = [1/(1 + t^2)] ρ0 [(x/(1 + t^2)) - t] satisfies the advection equation ∂ρ/∂t + v ∂ρ/∂x = -ρ ∂v/∂x.
The density of radioactive material, denoted by ρ(x,t), evolves according to the equation:
∂ρ/∂t + v ∂ρ/∂x = -ρ ∂v/∂x
This equation describes the transport of a substance by a moving medium, where the rate of movement of the radioactive material is influenced by the velocity of the wind, determined by the function v(x,t).
To solve the equation, we use the method of characteristics. We define the characteristic equation as:
x = ξ(t)
and
ρ(x,t) = f(ξ)
where f is a function of ξ.
Using the method of characteristics, we find that:
∂ρ/∂t = (∂f/∂t)ξ'
∂ρ/∂x = (∂f/∂ξ)ξ'
where ξ' = dξ/dt.
Substituting these derivatives into the original equation, we have:
(∂f/∂t)ξ' + v(∂f/∂ξ)ξ' = -ρ ∂v/∂x
Dividing by ξ', we get:
(∂f/∂t)/(∂f/∂ξ) = -ρ ∂v/∂x / v
Letting k(x,t) = -ρ ∂v/∂x / v, we can integrate the above equation to obtain f(ξ,t). Since f(ξ,t) = ρ(x,t), we can express the solution ρ(x,t) in terms of the initial value of ρ and the function k(x,t).
Now, let's solve the advection equation using the method of characteristics. We define the characteristic equation as:
x = x(t)
Then, we have:
dx/dt = v(x,t)
ρ(x,t) = f(x,t)
We need to find the function k(x,t) such that:
(∂f/∂t)/(∂f/∂x) = k(x,t)
Differentiating dx/dt = v(x,t) with respect to t, we have:
dx/dt = (2xt)/(1 + t^2) + 1 + t^2
Integrating this equation with respect to t, we obtain:
x = (x(0) + 1)t + x(0)t^2 + (1/3)t^3
where x(0) is the initial value of x at t = 0.
To determine the function C(x), we use the initial condition ρ(x,0) = ρ0(x).
Then, we have:
ρ(x,0) = f(x,0) = F[x - C(x), 0]
where F(ξ,0) = ρ0(ξ).
Integrating dx/dt = (2xt)/(1 + t^2) + 1 + t^2 with respect to x, we get:
t = (2/3) ln|2xt + (1 + t^2)x| + C(x)
where C(x) is the constant of integration.
Using the initial condition, we can express the solution f(x,t) as:
f(x,t) = F[x - C(x),t] = ρ0 [(x - C(x))/(1 + t^2)]
To simplify this expression, we introduce A(x,t) = (2/3) ln|2xt + (1 + t^2)x|/(1 + t^2). Then, we have:
f(x,t) = [1/(1 +
t^2)] ρ0 [(x - C(x))/(1 + t^2)] = [1/(1 + t^2)] ρ0 [(x/(1 + t^2)) - A(x,t)]
Finally, we can write the solution to the advection equation as:
ρ(x,t) = [1/(1 + t^2)] ρ0 [(x/(1 + t^2)) - A(x,t)]
where A(x,t) = (2/3) ln|2xt + (1 + t^2)x|/(1 + t^2).
Learn more about advection equation here :-
https://brainly.com/question/32107552
#SPJ11
185 said they like dogs
170 said they like cats
86 said they liked both cats and dogs
74 said they don't like cats or dogs.
How many people were surveyed?
Please explain how you got answer
185 said they like dogs, 170 said they like cats, 86 said they liked both cats and dogs, and 74 said they don't like cats or dogs. The number of people who were surveyed is 515.
The number of people who were surveyed can be found by adding the number of people who liked dogs, the number of people who liked cats, the number of people who liked both, and the number of people who did not like either. So, the total number of people surveyed can be found as follows:
Total number of people who like dogs = 185
Total number of people who like cats = 170
Total number of people who like both = 86
Total number of people who do not like cats or dogs = 74
The total number of people surveyed = Number of people who like dogs + Number of people who like cats + Number of people who like both + Number of people who do not like cats or dogs
= 185 + 170 + 86 + 74= 515
You can learn more about the survey at: brainly.com/question/31624121
#SPJ11
How do you know what method (SSS, SAS, ASA, AAS) to use when proving triangle congruence?
Answer:
Two triangles are said to be congruent if they are exactly identical. We know that a triangle has three angles and three sides. So, two triangles have six angles and six sides. If we can prove the any corresponding three of them of both triangles equal under certain rules, the triangles are congruent to each other. These rules are called axioms.
The method you will use depends on the information you are given about the triangles.
--> SSS(Side-Side-Side): If you know that all three sides of a triangle are congruent to the corresponding sides of another triangle, then the two triangles are congruent.
--> SAS(Side-Angle-Side): If you know that two sides and the angle between those sides are equal to the another corresponding two sides and the angle between the two sides of another triangle, then you say that the triangles are congruent by SAS axiom.
--> ASA(Angle-Side-Angle): If you know that the two angles and the side between them are equal to the two corresponding angles and the side between those angles of another triangle are equal, you may say that the triangles are congruent by ASA axiom.
--> AAS(Angle-Angle-Side): This method is similar to the ASA axiom, but they are not same. In AAS axiom also you need to have two corresponding angles and a side of a triangle equal, but they should be in angle-angle-side order.
--> RHS(Right-Hypotenuse-Side) or HL(Hypotenuse-Leg): If hypotenuses and any two sides of two right triangles are equal, the triangles are said to be congruent by RHS axiom. You can only test this rule for the right triangles.
Answer:
So, there are four ways to figure out if two triangles are the same shape and size. One way is called SSS, which means all three sides of one triangle match up with the corresponding sides on the other triangle. Another way is called AAS, where two angles and one side of one triangle match two angles and one side of the other triangle. Then there's SAS, where two sides and the angle between them match up with the same parts on the other triangle. Finally, there's ASA, where two angles and a side in between them match up with the same parts on the other triangle.